Propuesta de Plan de Mantenimiento Basado en Confiabilidad (RCM) para los Vehículos de la Empresa Arancel Servicios Logísticos y Financieros S.A.S (2022)
Currently, the vehicle fleet of Arancel Servicios Logísticos y Financieros S.A.S. is responsible for the transportation of different products within Colombia, amount ing to 540 tons per month of perishable food and beverages for breweries, being transported by three JAC trucks in an average time of 3 days per vehicle for a total of 10 to 9 trips per month. However, in recent years the company has not been able to adequ ately meet its commitments, mainly due to significant delays in providing the service, causing losses of 600,000 pesos per day for each truck that stops, resulting in the absence of important customers due to lack of credibility and efficiency. This situat ion is generated mainly by the increase in the level of breakdowns and inoperability of cargo transportation vehicles, raising considerably the repair costs. In view of this background, the objective of this research is to elaborate a maintenance plan fo cused on RCM applied to JAC vehicles of the company Arancel Servicios Logísticos y Financieros S.A.S., which allows guaranteeing the efficiency and quality of its performance. The methodology used complies with the requirements established by the standard and procedures for the development of a maintenance plan by RCM, taking into account stages and activities.